[PP.19.08] RETINAL CAPILLARY RAREFACTION IN PATIENTS WITH HYPERTENSION, TYPE 2 DIABETES MELLITUS AND HEALTHY CONTROLS. (September 2017) - Jumar, A.; Harazny, J.M.; Ott, C.; Striepe, K.; Karg, M.V.; Schmieder, R.E.
Abstract : Objective: Capillary rarefaction is increasingly believed to play a pivotal role in the pathogenesis of end-organ damage by affecting pressure and blood flow pattern. This severely affects peripheral vascular resistance (and thereby on systemic blood pressure), metabolisms and notably promotes tissue ischemia. We investigated retinal capillary density in patients with early disease of hypertension, diabetes mellitus type 2 (T2DM) and compared our results to healthy individuals. Design and method: This cross-sectional study compares retinal capillary rarefaction determined by intercapillary distance (ICD) and capillary area (CapA), measured non-invasively and in vivo by scanning laser Doppler flowmetry, in 134 individuals with hypertension stage 1 or 2, 73 patients with non-insulin requiring T2DM and 55 healthy controls. Results: Compared to hypertensive patients, diabetic individuals showed no difference in ICD (23.2 ± 5.5 vs 23.1 ± 5.8, p = 0.781) and CapA (1592 ± 595 vs 1556 ± 649, p = 0.768) after adjustment for differences in cardiovascular risk factors between the groups. In patients with T2DM, ICD was greater (23.2 ± 5.5 vs 20.2 ± 4.2, p = 0.013) and CapA smaller (1592 ± 595 vs 1821 ± 652, p = 0.019) than in healthy controls. Diabetic patients were separated in 40 patients with hypertension and well controlled blood pressure and 33 patients without hypertension. There was no significant difference in ICD (22.9 ± 5.6 vs 23.5 ± 5.5, p = 0.647) and CapA (1583 ± 566 vs 1600 ± 638, p = 0.901) between diabetic patients with hypertension compared to diabetic patients without hypertension. Conclusions: There was no difference in capillary rarefaction in patients with hypertension and patients in the early stage of T2DM. Patients with T2DM showed capillary rarefaction compared to healthy individuals.